2004
DOI: 10.1080/01443610410001685466
|View full text |Cite
|
Sign up to set email alerts
|

Emergency peripartum hysterectomy in a Nigerian hospital: a 20-year review

Abstract: Postpartum haemorrhage is a major cause of maternal morbidity and mortality and occasionally severe enough to warrant hysterectomy to prevent maternal death. Hysterectomy often is fraught with danger and regular audit is necessary to assist in the reduction of these dangers. A 20-year audit of all emergency peripartum hysterectomies, performed at Havana Specialist hospital Lagos, Nigeria, is reported. Of the 6599 deliveries and peripartum referrals seen during the period, 22 had an emergency hysterectomy as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 2 publications
5
27
2
Order By: Relevance
“…Relatively lower percentages of STAH have been reported in other studies elsewhere (Kastner et al 2002;Ezechi, et al, 2004;Selo-Ojeme et al, 2005;Ozden et al, 2005;Rahman et al, 2008). The decision to do total or subtotal emergency hysterectomy depends on the experience of the surgeon performing the operation and the condition of the patient.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Relatively lower percentages of STAH have been reported in other studies elsewhere (Kastner et al 2002;Ezechi, et al, 2004;Selo-Ojeme et al, 2005;Ozden et al, 2005;Rahman et al, 2008). The decision to do total or subtotal emergency hysterectomy depends on the experience of the surgeon performing the operation and the condition of the patient.…”
Section: Discussionmentioning
confidence: 82%
“…The incidence of emergency peripartum hysterectomy varies from 2 to 10 per 1000 deliveries (Engelsen et al, 2001;Okogbenin et al, 2003;Zamzami, 2003;El-Jallad et al, 2004;Kwame-Aryee et al, 2007). Some studies have reported excessive haemorrhage in the third stage of labour due to uterine atony or placenta praevia as the common indication for emergency peripartum hysterectomy (Zamzami, 2003;Ezechi et al, 2004) while other studies have shown ruptured uterus to be the common indication (Chew & Biswas, 1998;Okogbenin, et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In our study the mean maternal age was 26 years which is in contrast to many other studies where peripartum hysterectomy was done in women with mean maternal age >30 yrs. 8 This reflects the difference in the mean age of obstetric population at different places and countries and in developed countries the shift of maternal age towards elderly group is due to literacy and advancement in artificial reproductive technology.…”
Section: Resultsmentioning
confidence: 99%
“…Poręba et al, and Jagielska et at., in 90.6% and 87.5% of the surgeries [23,26]. Amputation of the uterine corpus is less challenging technically, and is connected with shorter procedure time, less blood loss, and fewer complications [1,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Amputation of the uterine corpus is technically less challenging, connected with shorter time of the procedure, less blood loss, and fewer complica-www. journals.viamedica.pl/ginekologia_polska tions [1,9,10]. The steadily growing rate of cesarean sections results in a higher number of obstetric hysterectomies.…”
Section: Introductionmentioning
confidence: 99%